2020
DOI: 10.1021/jacs.0c02075
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Assembly of Cycloenones with a Nitrile-Containing All-Carbon Quaternary Center from Malononitriles Enabled by Ni Catalysis

Abstract: Chiral nitriles are valuable molecules in modern organic synthesis and drug discovery. Selectively differentiating the two nitrile groups of widely available malononitrile derivatives is a straightforward yet underdeveloped route to construct enantioenriched nitriles. Here we report an enantioselective nickel-catalyzed desymmetrization of malononitriles for the generation of nitrile-containing all-carbon quaternary stereocenters. This protocol involves a nickel-catalyzed addition of aryl boronic acids to alkyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 60 publications
1
51
0
1
Order By: Relevance
“…Additionally, the isomerization of the putative 1,2‐disubstituted cis ‐alkenylnickel species to the corresponding trans one requires overriding the steric repulsion between the nickel and the substituent on the neighboring carbon [13] . Indeed, such isomerization of 1,2‐disubstituted alkenylnickel has been rarely investigated, although strategies involving cis / trans isomerization of fully substituted alkenylnickel species formed via alkyne insertion into arylnickel species and sequential cyclization were successfully demonstrated by Liu, [14] Lam, [15] and our group [16] . Gratifyingly, a preliminary proof was obtained by the use of Ni(OTs) 2 ⋅6 H 2 O as the nickel precursor predominately resulting endocyclic product 2 a with 97:3 er (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 95%
“…Additionally, the isomerization of the putative 1,2‐disubstituted cis ‐alkenylnickel species to the corresponding trans one requires overriding the steric repulsion between the nickel and the substituent on the neighboring carbon [13] . Indeed, such isomerization of 1,2‐disubstituted alkenylnickel has been rarely investigated, although strategies involving cis / trans isomerization of fully substituted alkenylnickel species formed via alkyne insertion into arylnickel species and sequential cyclization were successfully demonstrated by Liu, [14] Lam, [15] and our group [16] . Gratifyingly, a preliminary proof was obtained by the use of Ni(OTs) 2 ⋅6 H 2 O as the nickel precursor predominately resulting endocyclic product 2 a with 97:3 er (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 95%
“…Only a few examples using other arylboron reagents such as aryl pinacolboronates, aryl trifluoroborates, or arylboroxines have been reported. [68,73] In nickel-catalyzed arylative cyclizations of alkyne-tethered electrophiles, two modes of cyclization are generally possible, which differ in both their regio-and stereochemical outcomes. [90] The first of these is anti-arylmetallative cyclization.…”
Section: Mechanistic Aspects Of Nickel-catalyzed Arylative Cyclizationsmentioning
confidence: 99%
“…Pioneering studies by the Louie group have demonstrated the capability of nickel catalysis in coupling diynes and nitriles to construct pyridines. [40][41][42][43][44][45][46] Inspired by their mechanistic studies 44 and in line with our interest in desymmetrization, 47,48 we envisaged that an intramolecular hetero-cyclometallation of an alkyne-tethered malononitrile 1 with a nickel complex could form an aza-nickelacyclopentadiene (int II), followed by an alkyne insertion (int III) and reductive elimination to deliver enantioenriched fully substituted pyridines (Scheme 1F). We anticipated that the formation of the rigid five-membered ring-fused int II could facilitate the discrimination of the two CN groups efficiently.…”
Section: The Bigger Picturementioning
confidence: 99%